ANALISIS KUALITAS PELAYANAN IZIN USAHA PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN PATI - Feny Handayani; Nina Widowati; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The Office of Investment and One Stop Integrated Services (DPMPTSP) of Pati Regency support economic growth through business license services. However in the service process, there are problems such as unfulfilled infrastructure facilities, lack of clarity information provided, and not optimal handling of complaints and suggestions. The purpose of this study was analyze the quality of business license services at DPMPTSP Pati Regency, and identify it’s inhibiting factors. This study uses qualitative descriptive method. Based on the research results, in tangible dimension there are unfulfilled infrastructure and lack of officer discipline. In reliability dimension, service standards haven’t been updated and lack of staff capability. In responsiveness dimension, the complaint handling mechanism is less than optimal. In assurance dimension, timeliness, cost, and legality of licence have been guaranteed. In empathy dimension, the agency's interest has a higher bargaining position than the applicant's interest. There are inhibiting factors such as awareness factors, rules, organization, income, competency and service infrastructure factors. It can be concluded that the services provided by DPMPTSP Pati Regency do not have problems that occur in assurance dimension, but there are problems encountered in tangible, reliability, responsiveness, and empathy dimensions with the least problems in industrial business license service.